A Bi‐enzymatic Convergent Cascade for ε‐Caprolactone Synthesis Employing 1, 6‐Hexanediol as a 'Double‐Smart Cosubstrate'. Issue 16 (14th July 2015) - Bornadel, Amin; Hatti‐Kaul, Rajni; Hollmann, Frank; Kara, Selin
Abstract A bi‐enzymatic cascade consisting of a Baeyer–Villiger monooxygenase and an alcohol dehydrogenase (ADH) was designed in a convergent fashion to utilise two molar equivalents of cyclohexanone (CHO) and one equivalent of 1, 6‐hexanediol as a 'double‐smart cosubstrate' to produce ε‐caprolactone (ECL) with water as sole by‐product. The convergent enzymatic cascade reaction reported herein, is performed at ambient conditions in water, is self‐sufficient with respect to cofactor, and incorporates all starting materials into the desired product, ECL. Among different enzymes explored, the reaction catalysed by cyclohexanone monooxygenase from Acinetobacter sp. NCIMB 9871 coupled with ADH from Thermoanaerobacter ethanolicus showed the best results, reaching 91 % conversion of CHO after 24 h with a product titre of 2 g L−1. Scale‐up of the coupled system (50 mL) performed better than the small‐scale reactions and >99 % conversion of CHO and ECL concentration of 20 mM were achieved within 18 h.